The official GameSalad guide to game development - Novak, Jeannie, 1966- (Clifton Park, NY : Delmar, Cengage Learning, 2014)
The Official GameSalad Guide to Game Development prepares readers to create full-featured games with the simple, drag-and-drop GameSalad Creator software. Using proven techniques based on essential concepts, current trends, and established best practices, readers will learn how to create a real-world project from start to finish. The text's wide-ranging coverage encompasses desktop, mobile, online, social, and serious games -- as well as key platforms such as iOS, Android, Mac, Windows, and HTML5. This reader-friendly, highly visual guide is equally suited for formal game development courses and self-paced learning -- with a balance of depth, detail, and step-by-step guidance that is ideal for both professionals and enthusiasts interested in developing their own games. - Back cover.
Includes bibliographical reference (pages 219-225) and index.
Keywords: Computer games -- Programming; Computer games -- Design